KESADARAN HUKUM MASYARAKAT DALAM KEPEMILIKAN AKTA PERKAWINAN (Studi Kasus Di Desa Muara Musu Kecamatan Rambah Hilir Kabupaten Rokan Hulu) - Samroh Samroh; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by there are still people who do not have a marriage certificate in Muara Musu Village, Rambah Hilir District, Rokan Hulu Regency. The formulations of the research problems are: (1) What is the level of legal awareness of the community in ownership of a marriage certificate in Muara Musu Village, Rambah District, Rokan Hulu Regency, (2) What are the factors that influence under-handed marriage in Muara Musu Village, Rambah Hilir District, Rokan Hulu Regency. The research aims (1) to determine the level of legal awareness of the community in ownership of a marriage certificate in Muara Village, Rambah Hilir District, Rokan Hulu Regency, (2) to determine the factors that influence under-handed marriage in Muara Musu Village, Rambah Hilir District, Rokan Hulu Regency. The research was conducted in Muara Musu Village from September 2019-June 2020. This research is a quantitative descriptive study. With the entire population of Muara Musu Village and the sample using purposive sampling technique, with a sample of 34 people as respondents who have met the characteristics or criteria as a sample. Based on the results of the research, the problem formulation (1) the level of legal awareness of the community in ownership of a marriage certificate in Muara Musu Village, Rambah Hilir District, Rokan Hulu Regency is relatively high (2) the factors that affect under-handed marriage in Muara Musu Village, Rambah Hilir District, Rokan Hulu Regency are economic factors and biological factors. The results obtained in this study were the high level of community legal awareness in ownership of a marriage certificate in Muara Musu Village, Rambah Hilir District, Rokan Hulu Regency, so the hypothesis which states that the community's lack of legal awareness in ownership of a marriage certificate is rejected.Key Words: Legal Awareness, Marriage Certificate